The Correlation of Postpartum Depression, Breastfeeding Prevalence, and Milk Production in NICU - Sabrina, Mazaya Ilmi; Amaliya, Sholihatul; Kapti, Rinik Eko (Universitas Muhammadiyah Surakarta, 2025)
Breastfeeding is essential, particularly for newborns with severe health issues in the neonatal intensive care unit (NICU), where they frequently have to be separated from their mothers. Breastfeeding in the NICU requires a sufficient supply of breast milk from the mother, and this can be influenced by the mother's psychological condition. This study aimed to examine the correlation of postpartum depression with breast milk feeding prevalence and production in mothers with neonates in the NICU. This cross-sectional quantitative study included 42 mothers and infant dyads in the NICU in Malang, East Java, and was conducted between September and November 2024. The questionnaire of mothers and infants characteristics, the Edinburgh Postpartum Depression Scale, and the breast milk feeding prevalence observational sheet were used for the investigation. The correlation of postpartum depression with breast milk prevalence and breast milk production was measured by the Rank Spearman Test. Breast milk feeding prevalence was 64.3%, partial breast milk feeding was 31%, and formula milk was 4.8%. The proportion of mild and severe postpartum depression was 35.7%, and the rest of them were without depression (28.5%). Postpartum depression was not associated with the prevalence of breast milk feeding (p=0.140), but there was a significant correlation with breast milk production (p=0.04; r= -0.319). We found that greater postpartum depression was associated with lower breast milk production, but there was no correlation with the prevalence of breast milk feeding in the NICU. These ﬁndings highlight the importance of sufficient support for mothers with neonates in the NICU to produce enough breast milk supply.